THE EFFECTIVENESS OF THE CONTINUUM OF CARE-BASED MIDWIFERY CARE MANAGEMENT MODEL AS AN EFFORT TO REDUCE MMR, IMRAND INCREASE MKJP - Heni Frilasari (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Maternal health is one of the targets set in the 2030 Agenda 3 (Sustainable Development Goals), which targets a maternal mortality rate (MMR) of 70 per 100,000 live births. MMR in Indonesia remains relatively high and is a major health problem. One of the causes of MMR and an indirect cause of IMR is preeclampsia. Preeclampsia is a specific pregnancy-related hypertension syndrome with a multisystem, multifactorial condition that is significantly associated with maternal and perinatal mortality and morbidity. (Arti, Wijayati, and Ivantarina, 2022) The Continuum of Care-based Midwifery Care Management Model, which begins during pregnancy and continues through family planning, is an important strategy for improving maternal and infant health and reducing maternal and infant mortality rates (MMR) and infant mortality rates (IMR). This research uses a case study method, which describes the results of the assistance provided to respondents after treatment. The purpose of implementing this care is to identify the CoC care model in reducing MMR, IMR and increasing MKJP in respondents as many as 33 years old carried out for ± 8 weeks, including 2 pregnancy care, 1 delivery, 4 postpartum care, 3 neonatal care, and 1 family planning care. The results of pregnancy care were mostly normal without any complications 26 (78.7%), the majority of spontaneous deliveries 31 (94%), the majority of postpartum was normal without complaints and complications 32 (97%), the majority of babies were in normal condition 31 (94%) and the choice of contraception mostly used IUD 11 (33%). Midwifery care management based on the Continuity of Care approach contributes to reducing maternal and infant mortality rates and improving the well-being of mothers and babies, thereby supporting the achievement of optimal health. The target number of long-term family planning (MKJP) users is also met.